Sentir le traumatisme. Le sens de l’odorat dans Le Ciel de Bay City de Catherine Mavrikakis - Schincariol, Andrea (Ponti/Ponts, 2021)
Le Ciel de Bay City is the story of Amy, an American teenager haunted by the memory of the Holocaust. Her mother, Denise, and her aunt, Babette, miraculously survived the death camps. They took refuge in Bay City, a little town whose purple sky carries the toxic exhalations of Michigan automotive assembly plants. Every single night, while sleeping, Amy lives the tragedy of the Holocaust. Suddenly, her nightmares come true: her grandparents, Elsa and Georges, dead in Auschwitz, materialize in the basement. A musty smell, a smell of stale, coming from this basement, pollutes the entire house. The article studies the role of the odours in Mavrikakis’ novel. In particular, Schincariol focuses on the unveiling function of the olfactory paradigm. The smell reveals the memory of the concentration camps. The musty smell rising from the basement is the symbol of this traumatic truth.